2019
DOI: 10.1371/journal.pone.0218346
|View full text |Cite
|
Sign up to set email alerts
|

A new microbial gluten-degrading prolyl endopeptidase: Potential application in celiac disease to reduce gluten immunogenic peptides

Abstract: Gluten is a complex of proteins present in barley, wheat, rye and several varieties of oats that triggers celiac disease in genetically predisposed subjects. Gluten is notoriously difficult to digest by mammalian proteolytic enzymes and therefore, proline-rich digestion-resistant peptides contain multiple immunogenic epitopes. Prolyl endopeptidases (PEP) hydrolyse internal proline residues on the carboxyl side of peptides and have been proposed for food gluten detoxification and as oral enzyme supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…It has been shown that the human digestive tract has bacteria that can successfully break down and eliminate peptide fragments that are resistant to human peptidases (Caminero et al 2014;Herrán et al 2017). Extracellular protease genes are abundant in free-living bacteria (Nguyen et al 2019), and the most powerful proteases that degrade gluten are produced by microorganisms isolated from the surrounding environment (Mitea et al 2008;Amador et al 2019). Knowing that the diversity of human microbiome is decreasing as more people move away from nature (Grönroos et al 2019), it is tempting to hypothesize that there is a direct connection between gluten intolerance and a decrease in the available microorganisms capable of gluten destruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the human digestive tract has bacteria that can successfully break down and eliminate peptide fragments that are resistant to human peptidases (Caminero et al 2014;Herrán et al 2017). Extracellular protease genes are abundant in free-living bacteria (Nguyen et al 2019), and the most powerful proteases that degrade gluten are produced by microorganisms isolated from the surrounding environment (Mitea et al 2008;Amador et al 2019). Knowing that the diversity of human microbiome is decreasing as more people move away from nature (Grönroos et al 2019), it is tempting to hypothesize that there is a direct connection between gluten intolerance and a decrease in the available microorganisms capable of gluten destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches use peptidases from various sources such as fungi, bacteria, and germinated cereal grains (Curiel et al 2014;Guandalini and Assiri 2014;Wolf et al 2015;Scherf et al 2018;Schulz et al 2018). Postproline cutting prolyl endopeptidases from Sphingomonas capsulata, Flavobacterium meningosepticum, Myxococcus xanthus, Aspergillus niger, Flammulina velutipes, and Chryseobacterium taeanense, among others, have been pursued as drug candidates for the enzymatic treatment of gluten to treat celiac disease (Shan et al 2004;Mitea et al 2008;Schulz et al 2018;Amador et al 2019). Although many digestive enzyme supplements are ineffective in degrading immunogenic gluten epitopes, prolyl endopeptidase from Aspergillus niger is able to degrade toxic gluten epitopes (Janssen et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2RA3 revealed genes encoding proteases of the S9 family. A prolyl oligopeptidase was identified, and it degraded gluten immunogenic peptides in beer [36]. Then, we analyzed the genes catalyzing the hydrolysis of the C-N bond in the three B. cereus strains, and the number of those genes was similar among the three strains.…”
Section: Discussionmentioning
confidence: 99%
“…Gluten-degrading enzymes seem to hold the most promise as attractive therapies for helping patients with CD to avoid accidental gluten ingestion and to promote better overall health. A prerequisite is that such enzymes should be active under gastro-duodenal conditions, quickly neutralize the T-cell-activating gluten peptides and be safe for human consumption [ 67 , 68 , 70 , 109 ].…”
Section: Potential Alternative or Adjuvant Non-dietary Treatments For CDmentioning
confidence: 99%